Sex differences in the personal conceptions of intelligence: particularities of the Portuguese cultural context - Luísa Faria (2002)
Several empirical studies have implicated helplessness as a problem in girls' lack of achievement, generally associated with static conceptions of intelligence. Yet, two studies aiming to explore sex differences in personal conceptions of intelligence, carried out with Portuguese samples of 222 and 2,106 subjects, respectively, using a 15- item rating scale to measure personal conceptions of intelligence adapted for Portuguese adolescents (11 to 17 years old), did not find sex differences, suggesting that certain specific characteristics of the Portuguese cultural context and its underlying socialization processes may have altered the expected kind of differentiation. Researchers should investigate whether success is not stereotypically attributed to male role norms and the importance of arousal of standards of achievement for women in the Portuguese culture.